2013
DOI: 10.4172/2329-6895.1000137
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Short MRI Sequence Useful in Eliminating Stroke Mimics Among Acute Stroke Patients Considered for Intravenous Thrombolysis

Abstract: Background Acute stroke teams are challenged by IV-tPA decision making in patients with acute neurological symptoms when the diagnosis is unclear. The purpose of this study was to evaluate the ability of the rapid Brain Attack Team (BAT) MRI in selecting patients for IV-tPA administration who present acutely to the emergency room with stroke-like symptoms and an unclear diagnosis. Methods Consecutive patients were identified who presented within 4.5 hours of onset of stroke-like symptoms and considered for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Various studies have shown the feasibility of using specific MRI sequences as part of acute stroke protocols in patients eligible for IV tPA. 22 We propose that by modifying stroke pathway from algorithm I [CT+CTA≥IV tPA ± neuro-intervention≥ MRI] to algorithm II [Emergent MRI+MRA≥IV tPA ± Neuro-intervention], we can further reduce the cost in stroke pathways by $1,476 to $4,176 per patient by eliminating the cost of CT that was not calculated in our study.…”
Section: Discussionmentioning
confidence: 96%
“…Various studies have shown the feasibility of using specific MRI sequences as part of acute stroke protocols in patients eligible for IV tPA. 22 We propose that by modifying stroke pathway from algorithm I [CT+CTA≥IV tPA ± neuro-intervention≥ MRI] to algorithm II [Emergent MRI+MRA≥IV tPA ± Neuro-intervention], we can further reduce the cost in stroke pathways by $1,476 to $4,176 per patient by eliminating the cost of CT that was not calculated in our study.…”
Section: Discussionmentioning
confidence: 96%
“…The duration of imaging acquisition with MRI can also be reduced by applying a minimal imaging sequence protocol that may omit either perfusion, cerebral time-of-flight, or contrast-based cervical magnetic resonance angiography in early patients with clear IVT or endovascular treatment indications. 22–24…”
Section: Discussionmentioning
confidence: 99%
“…Despite this nonlinear trend, the median door-to-imaging delay was 27 minutes in both periods, and in the multivariable analysis the imaging paradigm did not have a significant effect (β-coefficient, 8.49 [95% CI, −1.94 to 18.93]; P adj =0.11; Table 2). In the subgroup of potential IVT candidates (patients arriving to the ER within 3.5 hours from known onset and with baseline National Institutes of Health Stroke Scale ≥4), the median delay to imaging was 2 minutes longer in the MRI-paradigm as opposed to CT-paradigm: 21 minutes (IQR, [16][17][18][19][20][21][22][23][24][25][26][27] The proportion of intracranial (±extracranial) arterial imaging with sufficient quality increased during the MRIparadigm (MRI-paradigm, 97.6% versus CT-paradigm, 92.9%; OR unadj , 3.06 [95% CI, 2.08-4.50]; P unadj <0.05) while the proportion of perfusion imaging at baseline with sufficient quality was similar (Table 2).…”
Section: Ais Diagnostic Workflowmentioning
confidence: 99%
“…However, given the aforementioned limitations in diagnosis, invasive testing, and treatment morbidity, we posit that MRI may have a role yet to play in ACS. We have seen how rapid MRI scans play an important role in acute brain ischemia, using abbreviated protocols to quickly discriminate between strokes to be treated with IV-tPA and stroke mimics [50]. Similarly, the shorter length of time from injury to fasciotomy portends a better outcome for patients with ACS.…”
Section: Diagnosis Of Compartment Syndromementioning
confidence: 99%